2016
DOI: 10.1371/journal.pone.0155137
|View full text |Cite
|
Sign up to set email alerts
|

Forest Owners' Response to Climate Change: University Education Trumps Value Profile

Abstract: Do forest owners’ levels of education or value profiles explain their responses to climate change? The cultural cognition thesis (CCT) has cast serious doubt on the familiar and often criticized "knowledge deficit" model, which says that laypeople are less concerned about climate change because they lack scientific knowledge. Advocates of CCT maintain that citizens with the highest degrees of scientific literacy and numeracy are not the most concerned about climate change. Rather, this is the group in which cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
14
1
2
Order By: Relevance
“…Hengeveld et al 2014), whether the owner is motivated by production or ecological values may still lead to diverse effects on the forest. Contrary to Blennow et al (2016) who found only marginal support for the importance of value profiles for belief in the local effects of climate change among forest owners in Sweden (environmentalists displayed a stronger belief) and no such connection among owners in Germany, the present study suggests that the importance of forest values for responses to climate change cannot be ruled out. Nevertheless, an encouraging social context may be even more important than forest values for climate change adaptation.…”
Section: Discussioncontrasting
confidence: 99%
“…Hengeveld et al 2014), whether the owner is motivated by production or ecological values may still lead to diverse effects on the forest. Contrary to Blennow et al (2016) who found only marginal support for the importance of value profiles for belief in the local effects of climate change among forest owners in Sweden (environmentalists displayed a stronger belief) and no such connection among owners in Germany, the present study suggests that the importance of forest values for responses to climate change cannot be ruled out. Nevertheless, an encouraging social context may be even more important than forest values for climate change adaptation.…”
Section: Discussioncontrasting
confidence: 99%
“…However, McCright and Dunlap [ 47 ] reported that the level of education in the United States is correlated with greater climate change risk perceptions only among liberals, but with a lower risk perception for conservatives, suggesting that higher education ultimately strengthens ideological views. This change in the sense of the interaction between education level and political view has not been observed for European forest owners [ 50 ], and we could not detect it in our dataset either, but attention should be paid to this possibility when designing awareness-raising campaigns.…”
Section: Discussionmentioning
confidence: 63%
“…Raftoyannis et al (2014) a mediterrán országokban vég-zett összehasonlító kutatásokat, vizsgálva a tűzbiztonsági intézkedések, a közvélemény figyelemfelkeltése és az üzemanyag használat szerepét az éghajlatváltozáshoz való adaptá-cióban. Blennow et al (2016) később arra hívta fel a figyelmet, hogy az erdészek között -a szakirodalomban a közvélekedéssel kapcsolatosan elterjedt összefüggéssel ellentétben -az egyetemi végzettség, a magasabb tudományos képzettség nem polarizálja az éghajlat-változásról való gondolkodást és a cselekvési hajlandóságot.…”
Section: Szakirodalmi áTtekintésunclassified